Maintenance treatment with H2 receptor antagonists in patients with peptic ulcer disease: rarely justified in terms of cost or patient benefit. Issue 6660 (26th November 1988) - Howden, C. W.
Abstract : Maintenance treatment reduces the frequency of ulcer relapse. Its routine use is unnecessary because the condition is benign and most patients do not relapse frequently. Routine maintenance treatment does not reduce the incidence of complications of ulcers overall, although it may do so in specific groups mentioned above. Routine maintenance treatment for all patients with ulcers would be expensive as well as largely unnecessary.